APROPRIASI BERAGAM FENOMENA KEHIDUPAN MAKHLUK HIDUP DALAM KARYA GRAFIS - Youngky Azhari; Budiwirman .; M. Nasrul Kamal (Universitas Negeri Padang, 2012)
Abstract Apropriation is a practice to create new art work by taking some art icons that already exist before. Phenomenon is the things that can be seeing by sight sense as show in some processes and also facts in human itself. Several phenomenons of creature are begun from they are still as a baby until they are mature enough as an adult, behavioural changes and so on. The description of this human life phenomenon is covered in graphic art work with the tittle: 1). Darwin’s Theory, 2). Butterflies, 3). Koi fish, 4). Reborn, 5). Arwana, 6). Frog, 7). Untitled, 8). Chameleon, 9). Go Green, 10). Kuli angkut. Art work that use Serigrapy technique, is the process where the printing process using silk, for instance monyl, and for drawing using rubber knive or rakel. Kata kunci : Apropriasi, Fenomena, Kehidupan, Makhluk Hidup, Grafis